Analysis of Student's Mathematical Creative Thinking Ability in Solving Open-Ended Problems in Terms of Cognitive Style - Amanah, Nabilla Nur; Inganah, Siti (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
The standards of education in the 21st century can think creatively. The ability to think creatively is an important aspect that must be developed and trained through problem-solving, one of which is open-ended. This study aimed to analyze students' creative thinking skills in solving open-ended problems in terms of their cognitive style. This descriptive qualitative study was conducted at SMP Muhammadiyah 1, Sumberpucung. The instruments used in this study were the GEFT to classify students with FI and FD cognitive styles, an essay test to measure students' mathematical creative thinking abilities, and an interview guide. The subjects of this study were students with FI and FD cognitive styles. Based on the GEFT test, it was found that out of 28 grade VIII students of SMP Muhammadiyah 1 Sumberpucung, 39.28% had the FI cognitive style, and 60.71% had the FD cognitive style. Four subjects with different cognitive styles were selected for interviews, and the results obtained were I1, I2, D1, and D2 at level 3 of the ability to think creatively, namely, creative. The four subjects met the indicators of fluency and flexibility but still lacked the originality indicator.